Religious Tolerance in the Digital Public Sphere: A Content Analysis of Log in Season 2 Episode 30 on Deddy Corbuzier’s YouTube Channel - Nur Fajriani; Hasan Basri M. Nur; Khairil Fazal (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2026)
The rapid development of digital spaces has not only enabled the dissemination of religious tolerance values but has also been marked by narratives of intolerance and identity-based conflicts. Although several studies have examined the Log In content, there remains a limited number of studies that specifically analyze the construction of tolerance materials within a single episode in depth. This study aims to analyze the construction of religious tolerance in Log-In Episode 30 Season 2 on Deddy Corbuzier’s YouTube channel from the perspective of digital da’wah. This research employs a library research design with a qualitative approach using content analysis of the video and audience responses. The findings reveal that tolerance is constructed through open dialogue, inclusive narratives, and communicative approaches that emphasize respect for differences. The messages represent the value of aqidah through the recognition of religious freedom and the value of akhlaq through polite, inclusive, and humanistic interactions. Positive audience responses indicate that dialogic digital da’wah is effective in strengthening public awareness of tolerance. This study contributes to the field of digital da’wah by demonstrating that social media can serve as a strategic medium for fostering religious harmony in a contextual and sustainable manner.